Improvement in Parameters of Patch Antenna By Using “Hybrid Shaped” Metamaterial Structure, “THIS PAPER HAS BEEN WITHDRAWN” - Garg, Bimal; Shrivastava, Himanshu; Kumar, Prem (International Journal of Engineering and Technology, 2012)
“THIS PAPER HAS BEEN WITHDRAWN”